Improving Performance through Leadership Agility, Organizational Support, and Organizational Commitment: An Integrated Approach - Suhermin, Suhermin; Rahayu, Rika; Shabrie, Wiwiek Srikandi (Image : Jurnal Riset Manajemen, 2024)
Organizational leaders determine the success of an organization towards optimal performance. Industry 4.0 requires organizational leaders who are agile and quick to adjust to change. The emphasis now is on the ability of leaders to adapt to changes in the environment and the new order in the business world. This study measures employee performance based on leadership agility, organizational support, organizational commitment, and performance. This research used a quantitative approach; more specifically, the quantitative approach used was quantitative causality. The population of this study were all employees of Juanda Airport with minimum criteria of high school education with a minimum work period of 2 years, as many as 240 people. The sampling technique used simple random samples. The sample size is calculated using the Slovin formula, obtained by 150 employees as a sample. The sampling technique used stratified random sampling. Data analysis techniques using path analysis. The results showed that Leadership agility positively and significantly affects organizational commitment and employee performance. Organizational support has a positive and significant effect on organizational commitment and employee performance, while organizational commitment significantly affects employee performance.